OVERVIEW OF THE SUCCESSFUL CORAL REEF MANAGEMENT IN INDONESIA - Suharsono, - (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2010)
Indonesia is the largest archipelagic country in the world, composed of 18,110 islands with a coastline of 108,900 km long, extending some 5000 km long and 2000 km wide located between Asia and Australia. Coral reefs have important meaning and value for the coastal communities in term of economic, social, and cultural conditions. About 1.5 million people are traditional fishermen who live in subsistence level and depend on their lives fully on coral reefs' resources. The Indonesian coral reef contributed 14% of the world, distributed unevenly from Sabang to Merauke with the highest concentration around Sulawesi and Maluku. The species richness and the biodiversity of the Indonesian corals amounted to 590 species belonging to 82 genera or about 80% of the currently existing coral species in the world. Monitoring program has been done from 1993 to 2010 and it shows the trend of improvement in the term of live coral cover. The condition of coral reefs in Indonesia taken from 84 locations and 1048 sites were 50.54% in excellent condition, 26.72% in good condition, 37.21% in fair condition, and 30.82% in bad condition. Improving trends in live coral cover across all project sites shows that the live coral covers has increased in all monitored sites across all project districts with average yearly live coral coverage increase is about 2-5%. The National Policy, Strategy, and Action Plan was established, with its main objective of managing the coral reef ecosystems based on the balance between conservation and utilization, and it was reflected in the Law No. 27 of 2007 concerning coastal management and small islands. The most remarkable result of the program is community awareness, namely the decrease of fishing activities shows that the destructive fishing activities in all project district are now non-existent of at a minimal level. A special text books on marine lives for elementary, secondary, and high school is the most widely adopted by local education service as a book of local content. Whereas institutional strengthening program constitutes the most difficult, energy and time consuming activities. It is due to the rivaly between the local institution and the lac of officials' and the communities' knowledge on the conservation based management principle.